KARYA ROH KUDUS YANG BERDAMPAK TERHADAP PEMBARUAN GEREJA MENGHADAPI PERUBAHAN BUDAYA - Dessy Sababalat; Martina Novalina; Anwar Three Millenium Waruwu; Jemy Saleky Combi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
Church renewal has become an urgent necessity in the contemporary era, marked by cultural challenges. This article examines the significant role of the Holy Spirit in the process of church renewal amidst declining congregational participation and changing societal demands. Through a qualitative literature review approach, this research identifies that the Holy Spirit serves not only as a source of spiritual strength but also as a Teacher, Comforter, and Spiritual Guide for believers. Amidst cultural dynamics, the Holy Spirit provides wisdom and impetus to maintain the church's relevance. The study highlights the Holy Spirit's influence in shaping church leadership and empowering individuals with spiritual gifts. The findings indicate that a profound understanding of the Holy Spirit's work can lead to significant renewal in church practices, strengthening ministries and honouring God. This article makes a vital contribution to understanding and practising church responses to contemporary challenges, emphasizing the importance of the Holy Spirit's role in sustaining church vitality amidst cultural shifts.